¡Múdate ya! - Baca Grández, Micaela Lucía (2025)
The artistic research project ¡Múdate ya! aims to question the development of architecture based on the market; analyze how the languages and aesthetics of real estate marketing reinforce hegemonic aspirational narratives; explore the organic emotional connections in a home built for its inhabitants; and denormalize the trend toward downsizing and standardization of housing in Metropolitan Lima. The materials used include thread and tracing paper, while the methods encompass drawing with machine stitching on paper and the comparison of case studies. The research is guided by the following question: does our way of living determine architecture, or does architecture determine our way of living?.